2000
DOI: 10.1034/j.1399-3011.2000.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the cyclization tendency of backbone cyclic tetrapeptides

Abstract: The cyclization kinetics of five backbone-cyclic tetrapeptides was investigated both experimentally and computationally. The aim was to both accurately measure the cyclization rates in solution and develop a method that efficiently estimates the relative cyclization tendencies computationally. Progression of the cyclization reaction was monitored directly, yielding the kinetics of changes in the amounts of the linear precursor and the products. These measurements were used to calculate the reaction rates; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…4C. The ''curved'' conformation, has been recognized as pre-requisite to be fulfilled in order to undergo cyclization [25]. Thus, molecules that are able to reach ''curved'' conformations have overcome the first conformational requirement for cyclization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4C. The ''curved'' conformation, has been recognized as pre-requisite to be fulfilled in order to undergo cyclization [25]. Thus, molecules that are able to reach ''curved'' conformations have overcome the first conformational requirement for cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Methodologies to predict the tendencies of peptides to undergo cyclization have been reported. [24,25] Based on molecular mechanics calculations and experimental evidence involving cyclotetrapeptides, Cavelier-Frontin et al [24] concluded that the determining factor for ring closure is the transition-state energy, wherein those peptides that are able to have transition-states in a low strain conformation have more chances to undergo cyclization. In a subsequent study Besser et al [24,25] developed a methodology based on the structural comparison between the conformations of the linear precursor and the conformation in the transition-state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, several attempts have been made to develop different types of backbone modification, including investigations on the use of different protecting group combinations, resins and linkers, but also optimised conditions for the peptide assembly and cyclization on the solid phase, the cyclization tendency, side reactions and chemical characterisation of backbone cyclic peptides have been described [30,31]. Furthermore, the method of backbone cyclization has been proven useful for systematic SAR studies of bioactive scaffolds of the peptide hormones substance P, bradykinin and somatostatin within the recently developed "Cycloscan" technology [32,33].…”
Section: Conformational Restriction By Different Types Of Cyclizationmentioning
confidence: 99%
“…For all 25 sequences, their probabilities of PCC formation were calculated, and it was shown that that correlation between the calculated probability and cyclization indeed exists. Although some computational studies of peptide cyclization have been reported, to the best of the authors’ knowledge, no predictive model has been rigorously tested against an experimental data set.…”
mentioning
confidence: 99%